The influence of promotion, service quality, and pricing on purchase decisions at Assalaam hypermarket - Hadi, Alfiansyah; Cahyani, Rusnandari Retno; Mutiasari, Annisa Indah (Institute of Computer Science (IOCS), 2024)
This study aims to determine the effect of promotion, service quality, and price on purchasing decisions at Assalaam Hypermarket. This research is descriptive with a quantitative approach. The population consists of consumers shopping at Assalaam Hypermarket, with a sample of 150 respondents selected using non-random sampling techniques. The results indicate that promotion, service quality, and price significantly affect purchasing decisions. The calculation results obtained from the F-value (20.695) exceed the F-table (2.67), with a significant value of 0.000 < 0.05. Among the three variables, service quality has the most dominant influence on purchasing decisions.